2018
DOI: 10.1111/asj.13089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three probiotic Bacillus on growth performance, digestive enzyme activities, antioxidative capacity, serum immunity, and biochemical parameters in broilers

Abstract: This study was conducted to evaluate the effects of three Bacillus strains on growth performance, digestive enzyme activities, antioxidative capacity, serum immunity, and biochemical parameters in broilers. A total of 360 one-day-old Ross 308 chicks were randomly allocated into four groups with three replicates per group (n = 30). The control group was fed a basal diet, whereas the other groups fed basal diet supplemented with either Bacillus subtilis natto or Bacillus licheniformis or Bacillus cereus (10 cfu/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 48 publications
6
46
1
3
Order By: Relevance
“…It is well-documented that selected Bacillus strains are used in probiotic preparations for broiler chicken diets because of their favorable growth performance, especially final body weight, BWG, and FCR [10,41]. The beneficial role of B. licheniformis on the performance parameters was shown in poultry nutrition, including broiler chickens [42], laying hens [43], as well as turkeys [44].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-documented that selected Bacillus strains are used in probiotic preparations for broiler chicken diets because of their favorable growth performance, especially final body weight, BWG, and FCR [10,41]. The beneficial role of B. licheniformis on the performance parameters was shown in poultry nutrition, including broiler chickens [42], laying hens [43], as well as turkeys [44].…”
Section: Discussionmentioning
confidence: 99%
“…Se ha reportado que algunos microorganismos probióticos tienen la habilidad de modificar las concentraciones de colesterol en sangre, a través de la disgregación de sales biliares en compuestos biliares libres o ligando directamente el colesterol proveniente de la dieta durante el proceso de digestión de las grasas, disminuyendo así la absorción de colesterol en el tracto gastrointestinal de las aves [24,25]. Al analizar los resultados obtenidos en el presente estudio, los niveles de colesterol y triglicéridos en sangre, fueron menores en aquellas aves que recibieron Bacillus subtilis en la dieta; estudios previos en los cuales se ha utilizado Bacillus subtilis como probiótico han mostrado resultados similares a los de este estudio [18,20,25,26,27]. Es importante resaltar que la glucosa es la principal fuente para la obtención de energía necesaria para llevar a cabo los procesos metabólicos del organismo implicados en el anabolismo, por lo cual sus concentraciones en sangre son un factor importante para el buen funcionamiento de las vías metabólicas implicadas en la acreción proteica del músculo [28].…”
Section: Resultsunclassified
“…En el presente estudio, el uso de Bacillus subtilis incrementó las concentraciones de glucosa en sangre de manera significativa con respecto a los demás tratamientos, lo cual concuerda con los resultados encontrados en algunos estudios, en donde las aves alimentadas con una mezcla comercial de probióticos presentaron niveles mayores de glucosa en comparación con aquellas aves que no recibieron probióticos [28,29]. Sin embargo, algunos estudios realizados en pollos de engorde han mostrado que el uso de Bacillus subtilis en el alimento disminuye de manera significativa los niveles de glucosa en comparación con aquellas aves que recibieron una dieta sin adición de ningún agente antimicrobiano en el alimento [26,27].…”
Section: Resultsunclassified
“…The decrease in UA was not considered to be pathological, because no symptoms, such as impaired growth performance, villous congestion and hemorrhage were observed. Many studies [ 28 , 29 ] have found the feed additives, such as probiotics, also decreased non-protein nitrogen in chicken blood, including uric acid, ammonia, and urea. Plasma AKP activity in broilers was higher after artificial infection [ 30 ] and previous work from this laboratory demonstrated that supplementation with protocatechuic acid lowered blood AKP, indicating less inflammation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%